Neuroprotective role of herbal alternatives in circumventing Alzheimer's disease through multi-targeting approach - a review. Issue 1 (31st December 2022) - K Ravi, Sunil; Narasingappa Ramesh, Balenahalli; Kj, Shilpa; Poyya, Jagadesha; Karanth, Jyothsna; Raju, N.G; G Joshi, Chandrashekhar
ABSTRACT: Alzheimer's disease (AD) is a common form of dementia affecting the elderly worldwide. It is a multifactorial neurodegenerative disorder with no known preventive therapy. Many of the drugs used in the treatment of AD, such as galantamine, rivastigmine, and donepezil, have unpleasant side effects, and hence physicians are keen to find alternatives. Research has shown that plants and their phytochemicals can alleviate AD. These plant products can act through various modes, such as inhibition of amyloid β, acetylcholine, and γ-secretase, modulation of antioxidants, and α-secretase activation, which are known to involve in the improvement of brain functions. A recent approach that has garnered the attention of many researchers in designing a drug against AD is the multi-target-directed ligand (MTDL), wherein the same molecule act on multiple targets. Many studies have reported the potential of herbs to act on multiple targets and display biological properties. The current review summarizes the ongoing evidence on the use of herbs and their derived bioactive molecules in the treatment of AD and in relieving disease-associated pathological events. Currently available plant-derived MTDLs for the treatment or slowing down of the progression of AD are also discussed.